Administrative and legal aspects of forensic expertise as a way to reduce corruption risks at the stage of amending a public procurement contract - Lezhnin, Volodymyr (Archives of Criminology and Forensic Sciences, 2024)
The article is devoted to the issues of reducing corruption risks when amending such an essential term of a procurement contract as the price. Statistical data and court practice on this issue are analysed. It compares the EU and Ukrainian legislation regulating the issue of contract price increase. The author identifies the contradictions in court practice regarding the appointment of an expert in the case of price fluctuations on the market. The article identifies gaps in the legal regulation of contract amendments in the case of price fluctuations in the market for works and services. The author provides an academic and legal assessment of the prohibition on increasing the total amount of a contract when there are document-ed reasons for increasing the unit price. It is proposed to specify the mechanisms for documenting price fluctuations in the market, including through forensic examination. The author substantiates the need to include thresholds for changing the price of a procurement contract in the legal regulation. It is proved the need to change the procurement legislation regulating the issue of contract price increase. Proposals for amending the current public procurement legislation are formulated.